Connections between Paweł Szymański's works and Ukrainian history and culture - Kostka, Violetta (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Three of Paweł Szymański’s works point out connections with Ukrainian history and culture. The documentary Schizophrenia, with soundtrack by the composer, tells about two Ukrainians, victims of psychiatric repressions in the Union of Soviet Socialist Republics. The main vocal part of the opera Qudsja Zaher was written especially for Olga Pasiecznik, an outstanding Ukrainian singer. The Concerto con duoi violini e Violoncello di Concertino obligati e duoi altri Violini, Viola e Basso di Concerto Grosso del Sig' Szymański was performed in Lviv during “Contrasts” festival in 2017.